2021
DOI: 10.1038/s41467-021-22867-w
|View full text |Cite|
|
Sign up to set email alerts
|

Single-component multilayered self-assembling nanoparticles presenting rationally designed glycoprotein trimers as Ebola virus vaccines

Abstract: Ebola virus (EBOV) glycoprotein (GP) can be recognized by neutralizing antibodies (NAbs) and is the main target for vaccine design. Here, we first investigate the contribution of the stalk and heptad repeat 1-C (HR1C) regions to GP metastability. Specific stalk and HR1C modifications in a mucin-deleted form (GPΔmuc) increase trimer yield, whereas alterations of HR1C exert a more complex effect on thermostability. Crystal structures are determined to validate two rationally designed GPΔmuc trimers in their unli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(85 citation statements)
references
References 109 publications
10
73
2
Order By: Relevance
“…Similar immunization protocols were reported in our previous vaccine studies ( 41 , 86 , 87 ). Briefly, the Institutional Animal Care and Use Committee (IACUC) guidelines were followed for all of the animal studies.…”
Section: Methodssupporting
confidence: 60%
See 3 more Smart Citations
“…Similar immunization protocols were reported in our previous vaccine studies ( 41 , 86 , 87 ). Briefly, the Institutional Animal Care and Use Committee (IACUC) guidelines were followed for all of the animal studies.…”
Section: Methodssupporting
confidence: 60%
“…S10F, right two). In our previous studies ( 86 , 87 ), a similar approach was applied to assess hepatitis C virus (HCV) and Ebola virus (EBOV) vaccine-induced B cell responses in the spleen, a major lymphoid organ ( 88 ), after mice received four intraperitoneal injections. We observed distinct B cell profiles associated with the viral antigen and NP platform ( 86 , 87 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HEK293 cell line is also a platform of interest for production of recombinant viral vectors and vaccines at the industrial scale, because the cells are easy to grow in suspension and can be adapted to serum-free medium. Current developments of human vaccines using HEK293 cells include the expression of glycoproteins for the treatment of infectious diseases, such as rabies [209] or Ebola virus [210]. A recent study of a vaccine candidate against Trypanosoma vivax showed that an invariant antigen expressed in HEK293 cells was able to induce protective immunity in mice [211], showing promising results as a vaccine candidate.…”
Section: Mammalian Cellsmentioning
confidence: 99%